2021
DOI: 10.15537/smj.2021.42.7.20210112
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of women diagnosed with breast cancer in Jordan

Abstract: Objectives: To evaluate the epidemiology, prognostic factors, and 5-year overall survival (OS) of females with breast cancer (BC) diagnosed between 2011 and 2014 in Jordan. Methods:A retrospective medical review of females who were diagnosed with BC between 2011 and 2014 at the 2 leading public health providers in Jordan was performed. The endpoint of the study was 2018. Data were extracted from the medical files between 2011 and 2018, including demographic clinical data on the patient level. Survival by age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…However, a study conducted between 2004 and 2008 in Iraq reported that 54.1% of patients were younger than 50 years old, indicating a shift in the age distribution of breast cancer cases in Iraq over time [20] . This trend is also observed in Jordan, where 53.7% of breast cancer patients were over the age of 50 [21] . Moreover, a multicentric, crosssectional study conducted at three hospitals in KSA from February 2019 to February 2020 reported that the risk of breast cancer increased with age in Saudi Arabia [22] .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, a study conducted between 2004 and 2008 in Iraq reported that 54.1% of patients were younger than 50 years old, indicating a shift in the age distribution of breast cancer cases in Iraq over time [20] . This trend is also observed in Jordan, where 53.7% of breast cancer patients were over the age of 50 [21] . Moreover, a multicentric, crosssectional study conducted at three hospitals in KSA from February 2019 to February 2020 reported that the risk of breast cancer increased with age in Saudi Arabia [22] .…”
Section: Discussionsupporting
confidence: 63%
“…For example, in a study by Mutar et al, invasive ductal carcinoma was the most common (81.4%), followed by invasive lobular carcinoma (6.9%) [19] . Similarly, in a study conducted in Jordan, 86.9% of patients had ductal carcinoma [21] . Another study conducted in Mexico found that 79% of patients had ductal histology [39] .…”
Section: Discussionmentioning
confidence: 79%
“…Health consumers look for care plans tailored to meet their cultural expectations [5] The Arab league consists of 22 countries with a massive socioeconomic range, yet linguistic, cultural, religious, and demographic cohesion exists. The majority of the Arab population consists of youth and children [6,7]. Beliefs and practices of Arabs are highly inspired by the principles of Islam [8].…”
Section: Introductionmentioning
confidence: 99%
“…To offer culturally competent care, healthcare providers must understand the culture and religion of the groups they are handling. Delivering culturally competent care is almost certainly not an easy task, but is still a very worthwhile one for both healthcare providers and women [6]. Unborn and newborn rights are defined in numerous ways, including through a wide spectrum of civil, cultural, economic, social, and political rights [15, 16].…”
Section: Introductionmentioning
confidence: 99%